2020
DOI: 10.3389/fevo.2020.00190
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Breeding in Years Following Drought in a Desert-Dwelling Cooperative Breeder

Abstract: Variation in weather patterns can influence reproductive effort and success not only within but also between breeding seasons. Where environmental conditions can be highly variable between years, the weather, and particularly extreme weather events such as heat waves and droughts, may exert a strong influence on reproductive effort (number of breeding attempts) and success (number of surviving young) from one breeding season to the next. We used a 15-year dataset for a cooperatively breeding bird, the southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 91 publications
2
34
0
Order By: Relevance
“…Previous research on this species has shown that high air temperatures during early development are associated with reduced provisioning rates to nestlings (Wiley and Ridley 2016), smaller nestlings (Wiley and Ridley 2016), reduced likelihood of fledging at least one chick per breeding attempt (Bourne, Cunningham, et al 2020a), lower recruitment of young into the adult population (Bourne, Cunningham, et al 2020c) and compromised adult foraging efficiency and body mass maintenance (du Plessis et al 2012). In short, pied babblers at our study site are likely to reproduce less successfully during droughts (Bourne, Cunningham, et al 2020b) and completely fail to fledge young at mean daily maximum air temperatures of > 38°C between hatching and fledging (Bourne, Cunningham, et al 2020a).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Previous research on this species has shown that high air temperatures during early development are associated with reduced provisioning rates to nestlings (Wiley and Ridley 2016), smaller nestlings (Wiley and Ridley 2016), reduced likelihood of fledging at least one chick per breeding attempt (Bourne, Cunningham, et al 2020a), lower recruitment of young into the adult population (Bourne, Cunningham, et al 2020c) and compromised adult foraging efficiency and body mass maintenance (du Plessis et al 2012). In short, pied babblers at our study site are likely to reproduce less successfully during droughts (Bourne, Cunningham, et al 2020b) and completely fail to fledge young at mean daily maximum air temperatures of > 38°C between hatching and fledging (Bourne, Cunningham, et al 2020a).…”
Section: Introductionmentioning
confidence: 64%
“…Higher rainfall often has a positive effect on nestling development (Wiley and Ridley 2016) and survival (Skagen and Yackel Adams 2012;Mares et al 2017), at least in arid and semi-arid ecosystems (Cumming and Bernard 1997;Hidalgo Aranzamendi et al 2019), although see Morganti et al (2017) and Cox et al (2019) for effects of rainy weather in temperate environments. Nestlings are substantially less likely to survive during droughts compared to wetter periods (Morrison and Bolger 2002;Conrey et al 2016;Cruz-McDonnell and Wolf 2016;Bourne, Cunningham, et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Adverse effects of climatic conditions on ∆M b and survival are likely to be driven primarily by physiological tolerance limits (Smit et al ., 2018) and resource constraints (Nowakowski et al ., 2018) acting on individuals, irrespective of the number of individuals present in their social group. Benefits of group living and cooperation, including load‐lightening and the production of more surviving young by larger groups, have been observed in pied babblers previously (Ridley, 2016; Wiley and Ridley, 2016; Bourne et al ., 2020a). Yet we show here that larger group sizes did not moderate the influence of high temperatures and drought on body mass change or survival.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to know e.g., how selection for temperature tolerance operates and manifests under such circumstances (cf. Burggren, 2018;Stillman, 2019), and whether there is compensatory breeding in long-lived species in the breeding season following an extreme weather event (sensu Bourne et al, 2020b) also in temperate areas. (vii) Heritability of temperature-induced effects: Studies on wild and domesticated animals show that key thermoregulatory traits, such as heat production, body temperature, and temperature tolerance, show moderate to high heritability (typically 0.4-0.6) (e.g., Bowen and Washburn, 1984;Ueno and Komiyama, 1987;Nilsson et al, 2009).…”
Section: Future Perspectivesmentioning
confidence: 99%